KAJIAN TEKNOLOGI DAN PROSPEK BUDIDAYA BAWANG MERAH LAHAN SUB OPTIMAL DI MUSIM PENGHUJAN UNTUK BENIH - Rajiman, Rajiman (Jurnal Ilmu-Ilmu Pertanian, 2017)
This study aims to determine the implementation of production technology and the potential of shallot cultivation of sub optimal land in the off season. The research was conducted in Sanden, Bantul from March to May 2017. This research used survey method. The sampling stage is the selection of villages and farmer groups conducted purposively. The number of samples is determined proportionally, while the sample determination is done by snowball sampling technique with 30 persons. The observation parameters of shallot yields were: diameter of tube, weight of tube, rotten / porous tube and weight shrinkage after being stored for 3 months. The data has been collected by descriptive analysis in tabulation form. The results showed that the technology used in the cultivation of shallots in the off season is not different from the in season. The varieties developed are biru, bima and tiron with 20 x 20 cm spacing, organic and inorganic fertilizer use. Implementation of technology in the off season roduces a product of 7,60 kwintal / hectare and lower than in the in season of 92,51 quintals/hectare. Characteristics of off-season shallot were: diameter 20,5 mm; Weight per tube 2,8 grams; Tubers porous / rotten very low (0%) and shrinkage store 25,25%. The result of shallot in the off season has the potential to be developed into seeds.